Randomized controlled evaluation of a group-based training for parents of adolescents with gaming disorder or social network use disorder - Brandhorst, Isabel; Lahres, Patrizia; Hanke, Sara; Batra, Anil; Renner, Tobias; Barth, Gottfried Maria; Lindenberg, Katajun; Vonderlin, Eva; Petersen, Kay Uwe (International journal of environmental research and public health, 2023)
Background: Internet Use Disorder (IUD), Gaming Disorder (GD), and Social Network Use Disorder (SNUD) are common phenomena among adolescents and young adults. Negative consequences of such disorders can be observed in the individuals themselves and in the family system. Although parents can influence their children in many ways, they are rarely considered in interventions. The present study examines the effectiveness of a group-based training for parents of adolescents with IUD, GD, or SNUD. Methods: A total of 76 parents of adolescents (12 to 20 years) were randomly assigned to the intervention group (IG) or the waiting list control group. Parents in the IG participated over eight weeks in six sessions of training (topics: psychoeducation, parenting behaviour, parent-child relationships, parent-child communication, and stress and relaxation). Questionnaires on adolescent symptomatology, parent-child relationships, and parental burden were collected before and after the intervention/waiting period. Results: The training reduced the IUD symptomatology of adolescents from the parents’ perspective. GD symptomatology improved for at-risk users, though not for pathological users. Some aspects of the parent-child relationships improved in the mothers’ judgment. Parental stress was already low before the training. Conclusions: The presented parent group training can be used to improve IUD symptomatology in adolescents and is effective in the context of early intervention for at-risk computer gamers.
Veröffentlicht: 24 December 2022
Gesehen am 05.09.2023